Qualidade de manteigas produzidas com leite de vacas Jersey sob diferentes níveis de óleo de girassol na dieta - Chaves, Brunele Weber (2014)
This study aimed to evaluate the quality of butters produced with Jersey cows fed different sunflower oil levels in the diet. Sunflower oil, rich in polyunsaturated fatty acids was fed to animals in order that these fatty acids were transferred (in the original form or partially biohydrogenated) milk and were therefore present in dairy products such as butter derivatives. We used eight Jersey cows under different sunflower oil levels in the diet (0, 2.3, 4.7 and 7.0%), totaling different levels of lipids in the diet (3.7; 64; 8.4 and 10.68% ether extract in dry matter) in Latin 4x4 square design, with experimental periods of 15 days, 10 days of adaptation and 5 days of data collection and milk. With the milk produced by these animals, in the last two experimental periods, butters were made. Butters were assessed for their quality and their oxidative stability in shelf life, with examinations at zero, 30, 60, 90 and 120 days from the making thereof. Obtained butters differentiated nutritional quality by altering the fatty acid profile, with greater involvement of beneficial fatty acids consumer health, mono- and polyunsaturated, including CLA (conjugated linoleic acid) and, at the same time with texture features suggesting a better spreadability therefore with greater acceptance by consumers. The drawback of the increase of polyunsaturated fatty acids is related to a lower oxidation stability, which was observed in elevation of the levels of thiobarbituric acid reactive species (TBARS) and changes in color and pH observed during analysis and which could jeopardize its shelf life.